IS CD38 EXPRESSION STILL RELEVANT PROGNOSTIC FACTOR IN CHRONIC LYMPHOCYTIC LEUKEMIA? - Trajkova, Sanja; Chevrevska, Lidija; Ivanovski, Martin; Simjanovska-Popova, Marija; Pivkova Veljanovska, Aleksandra; Dukovski, Dushko; Panovska Stavridis, Irina (Radiance Research Academy, 2014)
Introduction: There is a decade of investigations into the role of CD38 in B cell chronic lymphocytic leukemia (B-CLL). Significant percentage of CLL patients expressed transmembrane glycoprotein- CD38 on the surface of leukemic cells. Several published studies suggested that CD38 is accepted as a dependable marker of unfavorable prognosis and as an indicator of activation and proliferation of CLL cells. The aims of the present study were to establish the predictive value of the CD38 expression and to examine the relationship between CD38 positivity and other established prognostic markers in Macedonian CLL patients. Material and methods: Peripheral blood samples from 100 consecutive treatment naïve CLL patients were analyzed by flow cytometry for CD38 expression on CD5/19 leukemic cells. Various patients established prognostic characteristics and molecular markers were studied in correlation to time to treatment (TTT). The Kaplan-Meier method was used to construct survival curves, and the log-rank statistic was used to compare these curves. Results: CD38 was expressed in 61 % of the patients. Patients with high CD38 expression (30% or more) with high value of B2M and advance disease according to Binet had significantly shorter survival times (p= 0 .00001) and (p=0.00033) respectively. Multivariate analyses showed that CD38 expression is an important prognostic factor for shorter TTT associated high B2M level (P .000002), age(P.00000), gender(P.00000), lower hemoglobin level (P.00008 ),hepatomegaly (P.00086). Conclusion: CD38 expression identified a group of patients with aggressive disease that was considered by traditional staging to be early-stage disease (Rai stages 0-II or Binet A). Patients with CD38 samples have significantly aggressive disease regardless of their clinical stage. But today in era of molecular and genetics markers when CD38 is loosing it prognostic value in CLL patients prognosis, we propose serial analyses of the percentage of CD38+cells to be done, resembling indicators of leukemic cell proliferation and may signal clone evolution to a more aggressive state.
Keywords: CLL; CD38; prognosis